3D Printing of Bilineage Constructive Biomaterials for Bone and Cartilage Regeneration. (31st July 2017) - Deng, Cuijun; Yao, Qingqiang; Feng, Chun; Li, Jiayi; Wang, Liming; Cheng, Guofeng; Shi, Mengchao; Chen, Lei; Chang, Jiang; Wu, Chengtie
Abstract : Owing to the different biological properties of articular cartilage and subchondral bone, it remains significant challenge to construct a bi‐lineage constructive scaffold. In this study, manganese (Mn)‐doped β‐TCP (Mn‐TCP) scaffolds with varied Mn contents are prepared by a 3D‐printing technology. The effects of Mn on the physicochemical properties, bioactivity, and corresponding mechanism for stimulating osteochondral regeneration are systematically investigated. The incorporation of Mn into β‐TCP lowers the lattices parameters and crystallization temperatures, but improves the scaffold density and compressive strength. The ionic products from Mn‐TCP significantly improve the proliferation of both rabbit chondrocytes and mesenchymal stem cells (rBMSCs), as well as promote the differentiation of chondrocytes and rBMSCs. The in vivo study shows that Mn‐TCP scaffolds distinctly improve the regeneration of subchondral bone and cartilage tissues as compared to TCP scaffolds, upon transplantation in rabbit osteochondral defects for 8 and 12 weeks. The mechanism is closely related to the Mn 2+ ions significantly stimulated the proliferation and differentiation of chondrocytes through activating HIF pathway and protected chondrocytes from the inflammatory osteoarthritis environment by activating autophagy. These findings suggest that 3D‐printing of Mn‐containing scaffolds with improved physicochemical properties and bilineage bioactivities represents an intelligent strategy for regenerating osteochondral defects. Abstract : 3D‐printing of Mn‐TCP scaffolds can biologically fulfill the requirements for regeneration of both cartilage and subchondral bone simultaneously within osteochondral defects, offering a viable strategy for osteoarthritis treatment.